Do ethnicity and sex of employers affect applicants' job interest? An experimental exploration - Mark Granberg; Niklas Ottosson; Ali M. Ahmed (Journal for Labour Market Research, 2020)
Starting a business is one way out of unemployment for many people. Having a small pool of job applicants may, however, affect the quality of manpower available to employers. This paper reports the results of an experimental study that examined whether job-seekers discriminate against prospective employers based on those employers' ethnicity and sex. We conducted an experiment with 889 university students, where we presented 10 hypothetical job vacancies in the restaurant sector to the participants. We then asked participants to state their willingness to apply to each job. The ethnicity and sex of the employers were conveyed through employers' names by using typical male and female Arabic- and Swedish-sounding names. Overall, our results provided no evidence of ethnic or sex discrimination by job-seekers against employers.
Keywords: J71; J29; 330; Discrimination; Job search; Labor demand; Labor supply; Workers; Employers